THE EFFECTIVENESS OF WHATS'APP (WA) USERS IN CONVEYING INFORMATION AMONG STUDENTS MAJORING IN COMMUNICATION SCIENCES UIN NORTH SUMATRA - Robiatul Adawiyah Lubis; Muhammad Alfikri (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2022)
The purpose of this research is to find out how effective whats'app (WA) users are in conveying information among students majoring in communication science at UIN North Sumatra force 2018. This research uses qualitative research methods using a descriptive approach in their presentation. There are two sources of data used in this study, namely primary and secondary data. The primary data in this study is the result of observing the surroundings, interviews, and documentation. While secondary data is used to compare the theoretical perspective with the results of interview data. The technique of data accumulation (collection) is combined from the results of observations, documentation and interviews from class equipment and 2018 force Communication Science students at UIN North Sumatra. The data validity test is combined with the data accumulation technique, then analyzed and seen and assessed for the level of validity. Thus, the results of the study showed that the process of using WA in conveying information and communication among IKOM UINSU students was said to be effective and efficient. Where in its use and implementation it is faster to reach the intended person and practical to use, besides that WA is also very Accessibility and Functional. The obstacle that often occurs among students is the internet network which is sometimes slow, for friends who send messages to friends who are far from the city, must have a strong internet signal in order to get information.